Responding of Long Green Pepper Plants to Different Sources of Foliar Potassium Fertiliser - El-Mogy Mohamed M.; Salama Azza M.; Mohamed Hanaa F. Y.; Abdelgawad Karima F.; Abdeldaym Emad A. (Agriculture, 2019)
The aim of this study was to explore the efficiency of foliar potassium fertiliser relative to morphological, physiological and biochemical properties of hybrid long pepper (Capsicum annuum). Pepper plants were grown in a greenhouse and supplied with three sources of foliar potassium fertilisers, i.e., potassium-humate (1 g/L = 1,250 g/ha), potassium sulfate (1 g/L = 1,250 g/ha), and potassium chloride (1 g/L = 1,250 g/ha). Water served as control. The impacts of these treatments on the phytosynthetic parameters (photosynthetic rate, stomatal conductance, intercellular CO2, leaf carotenoids) and chlorophyll a and b, metabolic compounds and nitrogen, phosphorus and potassium were measured. The phytosynthetic parameters significantly improved by different foliar potassium application and the highest level of photosynthetic activity was noted in plants supplied with potassium sulfate, followed by potassium-humate and potassium chloride. Plant biomass accumulation, cholorophyll (a and b), and total yield showed larger increases in plants fertilised with potassium sulfate than those fertilised with potassium-humate; smallest increases occurred with potassium chloride. Concentrations of total sugars, carotenoids, chlorophyll (a and b), and endogenous level of nitrogen, phosphorus, and potassium contents in plants and fruits were possitively influenced by varying sources of potassium. The fruit color parameters and total soluble solid were also significantly increased with all foliar potassium treatments compared with control. Foliar application of potassium sulfate recorded the highest values and significantly increase all anatomical characters for leaf, stem and fruit of pepper plant.